The Institutional and Psychological Foundations of Natural Resource Policies. Issue 2 (1st February 2017) - Collier, Paul
A bstract: The pressures of political interests which drive the resource curse are well-understood. But ordinary citizens are usually cast both as the innocent victims of this process, and as the potential solution if only governments could be made more accountable to them. This paper draws upon recent developments in social psychology to discuss the formation of mass opinions on two aspects of resource ownership. One is the spatial assignment of ownership between local and national claims, which has been a significant cause of conflict. The other is the assignment of revenues between current consumption and future investment, which has usually been excessively biased towards the former. I suggest why, in the absence of an active government communications policy to offset them, known psychological biases may interact with resource discoveries to generate mass opinions which contribute to these problems.